Hubungan Bcs Dengan Kualitas Kolostrum Ditinjau Dari Solid Non Fat Dan Berat Jenis Kolostrum Sapi PFH - Zharfan Abdillah; Puguh Surjowardojo (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2018)
The reasearch was purposed to find out correlation about body condition score (BCS) of dairy cow on colostrum quality in terms of Solid Non Fat (SNF) and Specific Gravity. The material was used 30 pregnant of dairy cows with 9????ℎ months old. The method that used in the research was using survey and observation methods. Sampling was done by purposive sampling old pregnant dairy cows. The variables measured were Solid Non Fat (SNF) and Specific Grafity. Data were tabulated to SPSS 20 version, then analyzed descriptively and linear regression analysis using the SPSS program to determine the correlation of the old pregnant BCS of dairy cow on quality colostrum. The result showed an average was BCS 4, BCS of the old pregnant dairy cow showed a significant correlation (P<0.05) on quality of colostrum in terms of Solid Non Fat (SNF) with a correlation coefficient (r) = 0.749 and the determinantion coefficient (????2) = 56% and BCS of the old pregnant dairy cow showed a significant correlation to (P<0.05) on quality of colostrum Specific Grafity with a correlation coefficient (r) = 0.787 and the determinantion coefficient (????2) = 62% . It can be concluded a good BCS is a range of BCS (3-4), so that breeders should be controling the BCS of dairy cattle. If the value of BCS was great it make the higher quality of colostrum, so a new born calf will be grow well because the quality of colostrum was also great.